Assessment and the Journal of Clinical Child and Adolescent Psychology's Evidence Base Updates Series: Evaluating the Tools for Gathering Evidence. Issue 3 (4th May 2018) - Reyes, Andres De Los; Langer, David A.
Abstract : In 2014, Michael Southam-Gerow and Mitch Prinstein launched the Evidence Base Updates series. As invited contributors, authors of Evidence Base Updates articles offer the field an invaluable resource: regular evaluations of the latest data on tools for addressing the mental health needs of children and adolescents. Until now, authors of Evidence Base Updates articles have focused exclusively on evaluating treatment techniques. In this article, we outline how the Evidence Base Updates series will evolve to also include evaluations of assessment techniques. In our treatment-focused updates, contributors follow strict criteria when evaluating the evidence. Following these criteria allows authors of Evidence Base Updates articles to provide mental health professionals with clear "take-home messages" about the evidence underlying the treatments evaluated. Similarly, we outline the criteria that authors will follow when preparing Evidence Base Updates articles that evaluate assessments. We also highlight the formats of these articles, which will include evaluations of condition-focused measures (e.g., anxiety, conduct problems); transdiagnostic constructs (e.g., parenting, rumination); specific, widely used measures that cut across conditions; and updates on field-wide considerations regarding measurement (e.g., clinical utility, incremental validity).